MAKNA PRAGMATIS DALAM PERCAKAPAN NOVEL MENJARING SERIBU MIMPI KARYA MIRA KARMILA - Made Sri Indriani (Universitas Pendidikan Ganesha, 2012)
This study aimed at finding out the pragmatic meanings such as illocutionary forces, perlocutions,implicatures in conversations, presuppositions and deixises that occur in the conversations in the novel entitledMenjaring Seribu Mimpi. The study used a qualitive descriptive method. Notetaking technique was used totake a note of sentences that contain pragmatic meanings in the conversations. The result consists of a descriptionof sentences in the conversations that is followed by meanings that they convey. On the basis of the resultit can be concluded that the sentences used in the conversations contain locutions, illocution, perlocution,implicatures of the conversations, presuppositions and deixises. The findings in this study show that illocutionsin the conversations in the novel convey meanings such as commands, requests, offers and treats. On theother hand, the implicatures of the conversations include ‘I want to treat you’, ‘Please wait for me,’ ‘I wantto be your love,’ ‘I will prepare your meal,’ ‘Please go away from my sight, ‘have a break.’ Then the presuppositionsinclude ‘you have just had a program,’ ‘You were not at home,’ ‘ You are a grown – up,’ ‘Dady hadgot a meal,’ ‘You once saw me.’ You were well then.’ The deixeses are dominated by anaphore in the form ofthe first personal pronoun ‘I’ such as ‘saya’, ‘ku’, and ‘aku,’ the second personal pronoun such as ‘kamu’ and‘nya’ for the third personal pronoun. It is hoped that these results make a contribution in the educational field,particularly, in the teaching of Indonesia in the area of pragmatics.Keywords: pragmatic meaning, illocution, implicature of conversation, presupposition, deixis